PENGARUH KOMPENSASI FINANSIAL DAN KOPENSASI NONFINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN - Jaenab (Universitas Mahendradatta, 2021)
This study aims to explain the effect of variable financial compensation and nonfinancial compensation on employee job satisfaction simultaneously and partially. This study uses an explanatory research method with a quantitative approach. The population in this study were 36 employees and the research sample used was a saturated sample of 36 employees at PT. Kawi brilliant Bima. The analysis used is multiple linear regression. The results of the study simultaneously show that financial compensation and non-financial compensation have a significant effect on employee job satisfaction. Sig value. The F which is obtained is 0,000. The results of the study partially show that financial compensation has no significant effect on employee job satisfaction with a sig value. t of -283. The result of the research is partially known that non-financial compensation has a significant effect on employee job satisfaction with a sig.t value of 5,563